The implementation of the regional development index in the new geo-political context - Ionescu, Romeo-Victo; Zlati, Monica Laura; Antohi, Valentin-Marian; Cornea, Valentina; Socoliuc, Mihaela-Ionela (Technological and Economic Development of Economy, 2023)
The opportunity of this research topic lies in the current extremely challenging geopolitical context that has led to the outbreak of multiple crises: energy, economic, social, financial, food, etc. The European Union has thus positioned itself in the face of these phenomena by creating several instruments to manage crises and increase resilience: civil protection mechanism, integrated mechanism for political response to crises, cross-border cooperation and solidarity mechanisms, food security crisis plans, resilience measures against physical and digital risks.The paper aims to analyse the necessity of changing the regional approach across the EU under the impact of the pandemic. Specific regional socio-economic indicators for EU NUTS2 regions are analysed during 2010–2021. The main objective of this research is to quantify the regional socioeconomic and to realise comparative analysis related to three moments in time: the latest EU enlargement, the economic crisis and the pandemic. The novelty of the study was the building of a new dynamic multi-criteria model assessing the strategic perspective, which was built to offer pertinent solutions for the regional decision makers in order to ensure cohesion and sustainable development on short and medium term. First published online 25 August 2023